Service Oriented Architecture adaptation challenges - Paunisaari, Juha (2005)
This thesis deals with challenges in Service Oriented Architecture adaptation at the enterprise IT level. Today s IT managers are phasing very rapidly changing world in terms of the business and technology side. The Service Oriented architecture (SOA) has been one of the latest hot topics. Many articles have been written but still limited numbers of companies have used the SOA in the mission critical solutions. Software vendors are promoting the SOA and many parallel standardization efforts are progressing. This paper investigate the challenges the companies are facing when starting to use SOA for legacy application integration. An overview of SOA is given and relationship of SOA to EAI and Web Services. In the SOA adaptation challenges, the new technology adaptations challenges, Enterprise Application Integration (EAI), Service Oriented Architecture (SOA) and Web Services challenges were studied based on the written material. One of the major conclusions was that the challenges are not just technology related but many organizational issues were brought up.